Interregional contact and the formation of a shared identity - Manuel F. Bagues; Christopher Roth (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We study the long-run effects of contact with individuals from other regions in early adulthood on preferences, beliefs and national identity. We combine a natural experiment, the random assignment of male conscripts to different locations throughout Spain, with tailored survey data. Being randomly assigned to complete military service outside of one's region of residence fosters contact with conscripts from other regions, and increases sympathy and trust towards people from the region of service, as measured decades later. We also observe a long-lasting increase in identification with Spain for individuals originating from regions with strong peripheral nationalism.
Keywords: R23; D91; Z1; 330; Interregional Contact; Intergroup Exposure; Beliefs; Preference Formation; Identity